Extraction of Fast Changes in the Structure of a Disordered Ensemble of Photoexcited Biomolecules - H.-C. Poon; M. Schmidt; D. K. Saldin (Advances in Condensed Matter Physics)
Using pump-probe experiments of varying time intervals between pump and probe, the method of time-resolved crystallography has given many insights into the fast time variations of crystallized molecules as a result of photoexcitation. We show here that quantities extractable from multiple diffraction patterns of dissolved molecules in random orientations, as measured using powerful ultrashort pulses of X-rays, also contain information about structural changes of a molecule on photoexcitation.